Christ the light : the theology of light and illumination in Thomas Aquinas - Whidden, David L., III (Fortress Press; Minneapolis, 2014)
In Christ the Light, Whidden argues that illumination is a critical systematic motif in Aquinas' theology, one that involves the nature of truth, knowledge, and God; at the root, Aquinas' theology of light, or illumination, is Christological, grounding human knowledge of God and eschatological beatitude. This volume establishes the theological network formed by the crucial motif of light/illumination in Aquinas, from how theology operates to the systematic, sacramental, and moral coordinates in Aquinas' theology.
Includes bibliographical references (pages 223-241) and index.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Jesus Christ; Jesus Christ; Thomas / Aquinas, Saint / 1225?-1274 / Criticism and interpretation; Jesus Christ..; Thomas, -- Aquinas, Saint, -- 1225?-1274..; Thomas, -- von Aquin, Heiliger, -- 1225-1274.; Light -- Religious aspects -- Christianity; Light -- Religious aspects -- Christianity; Light -- Religious aspects -- Christianity..; Christologie..; Erleuchtung..; Licht..; Theologie..